Religion in consumer society: brands, consumers, and markets - Gauthier, François; Martikainen, Tuomas (Ashgate AHRC / ESRC religion and society series, 2013)
Presenting an overview of an emerging field in the study of contemporary religion, this book explores religion as both shaped by consumer culture and as shaping consumer culture. Following an introduction which critically analyses studies on consumer culture and integrates scholarship in the sociology of religion, this book explores religion, neoliberalism and consumer society. Claiming that we have entered a new phase that implies more than the recasting of state-religion relations, the authors examine how religious changes are historically anchored in modernity but affected by the commoditiz